Was the Cat in the Hat black? : the hidden racism of children's literature, and the need for diverse books - Nel, Philip, 1969- (New York, NY : Oxford University Press, 2017)
Racism is resilient, duplicitous, and endlessly adaptable, so it is no surprise that America is again in a period of civil rights activism. A significant reason racism endures is because it is structural: it's embedded in culture and in institutions. One of the places that racism hides -- and thus perhaps the best place to oppose it -- is books for young people. Philip Nel presents five serious critiques of the history and current state of children's literature tempestuous relationship with both implicit and explicit forms of racism. Nel examines topics both vivid -- such as The Cat in the Hat's roots in blackface minstrelsy -- and more opaque, like how the children's book industry can perpetuate structural racism via whitewashed covers even while making efforts to increase diversity. Rooted in research, Nel delves into years of literary criticism and recent sociological data in order to show a better way forward. Though much of what is proposed here could be endlessly argued, the knowledge that what we learn in childhood imparts both subtle and explicit lessons about whose lives matter is not debatable. The text concludes with a proposal of actions everyone -- reader, author, publisher, scholar, citizen -- can take to fight the biases and prejudices that infect children's literature.
Introduction: Race, racism, and the cultures of childhood -- The strange career of The Cat in the Hat; or, Dr. Seuss's racial imagination -- How to read uncomfortably: Racism, affect, and classic children's books -- Whiteness, nostalgia, and fantastic flying books: William Joyce's racial erasures vs. Hurricane Katrina -- Don't judge a book by its color: The destructive fantasy of whitewashing (and vice-versa) -- Childhoods "outside the boundaries of imagination": Genre is the new Jim Crow -- Conclusion: A manifesto for anti-racist children's literature.
Includes bibliographical references (pages 241-262) and index.
Keywords: Children's literature, American -- History and criticism; Race in literature; Racism in literature; LITERARY CRITICISM -- Children's & Young Adult Literature